GAYA KEPEMIMPINAN TRANSFORMASIONAL, INNOVATIVE WORK BEHAVIOR PEKERJA MUDAH SEKTOR RETAIL YANG DIMEDIASI KNOWLEDGE SHARING - Reginaldo Shevcenko; Tjahjoanggoro; Constantinus Wahju Prijonggo (CALYPTRA, 2025)
Abstract—The Innovative Work Behavior (IWB) exhibited by fresh graduate employees is crucial for companies as a strategy for success in today's competitive business environment. IWB can be influenced by transformational leadership and knowledge sharing. This research aims to examine the relationship between transformational leadership and Innovative Work Behavior (IWB) among fresh graduate employees in the retail industry. This study also tests the mediating role of knowledge sharing in this relationship. The research employs a quantitative method with accidental sampling involving 104 respondents of fresh graduate workers. The study utilizes the Innovative Work Behavior Scale (IWBS), Multifactor Leadership Questionnaire 5x (MLQ 5x), and Knowledge Management Scan (KMS) as measurement tools. Data is collected through questionnaires and analyzed using regression analysis. The findings of the study reveal a positive relationship between transformational leadership and Innovative Work Behavior (IWB). The study also confirms that knowledge sharing plays a significant mediating role (p < 0.05) in this relationship. The implications of these findings are valuable for the retail industry in formulating strategies to enhance the innovative work behavior of new graduate employees. The role of knowledge sharing as a mediator in this study is partial in connecting transformational leadership and Innovative Work Behavior (IWB) (z= 5.731; p=0.001). Hypothesis testing supports previous research findings, confirming that transformational leadership supports the practice of knowledge sharing (KS) and Innovative Work Behavior (IWB) in the workplace. Thus, this study has both theoretical and practical benefits for universities, employees, and company leaders in the retail sector. Keywords: transformational leadership, innovative work behavior (iwb), fresh graduate, retail & fmcg, knowledge sharing Abstrak—Penelitian Innovative Work Behavior (IWB) yang dimiliki oleh pekerja fresh graduates dibutuhkan oleh perusahaan sebagai strategi keberhasilan persaingan kompetitif pada era saat ini. Innovative Work Behavior sendiri dapat dipengaruhi oleh gaya kepemimpinan transformasional dan knowledge sharing. Penelitian ini bertujuan untuk menguji hubungan antara kepemimpinan transformasional dan innovative work behavior (IWB) pada karyawan fresh graduates di industri retail. Studi ini juga menguji peran mediasi knowledge sharing dalam hubungan tersebut. Penelitian ini dilakukan dengan metode kuantitatif dengan accidental sampling yang melibatkan 104 responden pekerja fresh graduates. Penelitian dilakukan dengan alat ukur Innovative Work Behavior Scale (IWBS), Multifactor Leadership Questionnaire 5x (MLQ 5x), dan Knowledge Management Scan (KMS). Data dikumpulkan melalui kuesioner dan dianalisis dengan analisis regresi . Temuan penelitian menunjukkan hubungan positif antara kepemimpinan transformasional dan innovative work behavior (IWB). Studi ini juga mengkonfirmasi bahwa knowledge sharing berperan sebagai mediator yang signifikan (p <0,05) dalam hubungan tersebut. Implikasi temuan ini berguna bagi industri retail untuk merumuskan strategi meningkatkan perilaku kerja inovatif karyawan baru lulus. Peran knowledge sharing sebagai mediator pada penelitian ini bersifat parsial dalam menghubungkan gaya kepemimpinan transformasional dan innovative work behavior (IWB) (z= 5,731 ; p=0,001). Uji hipotesis mendukung temuan penelitian sebelumnya, mengonfirmasi bahwa kepemimpinan transformasional mendukung praktik knowledge sharing (KS) dan innovative work behavior (IWB) di tempat kerja, sehingga memiliki manfaat teoritis dan praktis bagi universitas, pekerja, atasan perusahaan sektor retail. Kata kunci: transformational leadership, innovative work behavior(iwb), fresh graduate, retail & fmcg, knowledge sharing